ESSENCE AND VALUE OF STRATEGIC MANAGEMENT BY THE ORGANIZATION - N. N. Voroshilina (Современная наука и инновации)
Strategic management as an effective control mechanism should strengthen the position of the organization in the market and to ensure coordination, involvement and satisfaction of consumers, successful competition and achievement of global goals. Strategic management primarily depends on the skills of enterprise management personnel, which focuses on socio-economic activities on the needs of the population that responds flexibly to changes in the environment of the enterprise, allows to achieve a competitive advantage. Features of the development of the modern market require a special relationship with the consumer, quick changes and the presence of several costed options for further action. Today the key to successful and sustained development of any business is an effective strategy: realistic, "tied" to the resources of the organization, flexible, simple and understandable for managers of different levels containing the novelty and competitive advantage